Ty Doan: capstone - Doan, Ty, artist (Colorado State University. Libraries, 2026)
The artist's statement: My work explores branding as a way to build connection through place, culture, and shared experiences. I'm drawn to creating full brand systems that go beyond a logo and become something people can connect with through products, environments, and storytelling. A lot of my inspiration comes from the people and experiences that have shaped me. Growing up surrounded by my mom's artwork pushed me to think creatively from an early age and helped shape how I see visual storytelling. At the same time, working on hands-on projects with my dad taught me the value of craftsmanship and creating something with intention. My love for fly fishing and sports has also influenced how I think about community, place, and the experiences that bring people together. My process is very hands-on and often begins with pen and paper or sketching digitally on my iPad before moving into final execution. I enjoy slowing down and putting real care into work that feels crafted rather than rushed. Through branding, packaging, publication design, and illustration, I aim to create work that feels authentic and immersive. I want the things I create to feel personal while still existing as strong commercial products people can connect with.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design